Bacterial infection‐triggered acute‐on‐chronic liver failure is associated with increased mortality. (15th September 2017) - Mücke, Marcus M.; Rumyantseva, Tatiana; Mücke, Victoria T.; Schwarzkopf, Katharina; Joshi, Sabrina; Kempf, Volkhard A. J.; Welsch, Christoph; Zeuzem, Stefan; Lange, Christian M.
Abstract: Background & Aims: Acute‐on‐chronic liver failure (ACLF) is characterized by an acute deterioration of liver function in patients with cirrhosis in combination with recently defined organ failures. Our aim was to independently validate the prognostic value of the recently established EASL‐CLIF‐Consortium definition of ACLF and to identify new predictors of short‐term mortality. Methods: Patients with cirrhosis and the International Classification of Diseases, Tenth Revision diagnosis of (sub)acute liver failure were retrospectively categorized according to the EASL‐CLIF‐Consortium definition. Logistic regression analyses were performed to identify clinical and epidemiological predictors of 30‐ and 90‐day mortality. Results: From 2008 to 2015, 257 patients were included. Overall, 173 (67%) patients met the EASL criteria for ACLF (grade 1: n = 43 [25%], grade 2: n = 52 [30%], grade 3: n = 79 [45%]). Mortality within 30 days in patients without ACLF was 3.6%, and 18.6%, 37.3% and 62.0% in patients with ACLF grades 1, 2 and 3 respectively. Outcome of patients with bacterial infection‐triggered ACLF was distinct from non‐infection‐triggered ACLF (71.6% vs 33.8% 30‐day survival, P  < .001), and infection‐triggered ACLF was independently associated with increased mortality (odds ratio [OR] = 4.28, P  < .001). Pneumonia was a particularly frequent infection and burdened with high mortality. In addition, infections with multidrug‐resistant organisms were frequent and independently associated with mortality ( P  = .030, OR = 4.41), as was glycopeptide antibiotic therapy as initial empirical antibiotic therapy ( P  = .005). Conclusions: This study confirmed the EASL‐CLIF‐Consortium definition of ACLF as strong predictor of mortality in patients with acute decompensation of cirrhosis. However, we have observed a remarkably higher mortality in infection‐triggered ACLF compared to other precipitating events.